Phytonanoparticles as novel drug carriers for enhanced osteogenesis and osseointegration - Nandita Suresh; Nebu George Thomas; Matti Mauramo; Tuomas Waltimo; Timo Sorsa; Sukumaran Anil (Discover Nano)
Abstract Phytonanoparticles have emerged as a promising class of biomaterials for enhancing bone regeneration and osseointegration, offering unique advantages in biocompatibility, multifunctionality, and sustainability. This comprehensive review explores the synthesis, characterization, and applications of phytonanoparticles in bone tissue engineering. The green synthesis approach, utilizing plant extracts as reducing and stabilizing agents, yields nanoparticles with intrinsic bioactive properties that can synergistically promote osteogenesis. We examine the mechanisms by which phytonanoparticles, particularly those derived from gold, silver, and zinc oxide, influence key molecular pathways in osteogenesis, including RUNX2 and Osterix signaling. The review discusses advanced strategies in phyto-nanoparticle design, such as surface functionalization and stimuli-responsive release mechanisms, which enhance their efficacy in bone regeneration applications. Preclinical studies demonstrating improved osteoblast proliferation, differentiation, and mineralization are critically analyzed, along with emerging clinical data. Despite promising results, scalability, standardization, and regulatory approval challenges persist. The review also addresses the economic and environmental implications of phyto-nanoparticle production. Looking ahead, we identify key research directions, including developing personalized therapies, combination approaches with stem cells or gene delivery, and long-term safety assessments. By harnessing the power of plant-derived nanomaterials, phytonanoparticles represent an innovative approach to addressing the complex challenges of bone regeneration, with potential applications spanning dental, orthopedic, and maxillofacial surgery. Graphical abstract